General Characteristics of Preliminary Investigations in The Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Criminal procedure is a special area of the relationship between the individual and the state. The specificity of these relationships is manifested, first of all, in a certain inequality between the citizen and the complex system of the state machine, and this applies equally to both the accused (defendant) and the victim. This, by the way, determines the importance of studying the preliminary investigation, the peculiarities of the procedure for its implementation. The relevance of the research in this scientific article is also due to the fact that, despite the practical applicability of the institution of preliminary investigation in Uzbekistan, its theoretical component, coverage of the largest number of aspects of its conduct is currently insufficient.